2010
DOI: 10.1111/j.1540-8167.2009.01716.x
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Cardioverter‐Defibrillator in Patients With Hypertrophic Cardiomyopathy: Efficacy and Complications of the Therapy in Long‐Term Follow‐up

Abstract: ICD therapy is effective in SCD prevention in patients with HCM, although the complication rate is significant. Nonsustained ventricular tachycardia seems to be the most predictive RF for appropriate device discharges. Number of RF did not impact the incidence of appropriate ICD interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 36 publications
6
54
0
8
Order By: Relevance
“…Similarly, inappropriate shocks occurred at a rate of 4.9% (95% CI: 3.9-6.0) per year (I 2 =75%) ( Figure 3). Among six studies (7,8,10,25,29,33), heart transplant was required in 1.6% of patients per year. The annual incidence of lead malfunction and lead displacement was 1.4% (95% CI: 0.8-2.5) and 1.3% (95% CI: 0.8-2.0) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, inappropriate shocks occurred at a rate of 4.9% (95% CI: 3.9-6.0) per year (I 2 =75%) ( Figure 3). Among six studies (7,8,10,25,29,33), heart transplant was required in 1.6% of patients per year. The annual incidence of lead malfunction and lead displacement was 1.4% (95% CI: 0.8-2.5) and 1.3% (95% CI: 0.8-2.0) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of sudden death in HCM is low, around 0.7-1% per annum, and often young patients are affected (2). The use of implantable cardioverter-defibrillator (ICD) protects against SCD secondary to ventricular tachycardia (VT), ventricular fibrillation (VF), or bradycardia, with excellent results (3)(4)(5)(6)(7)(8). A major concern with ICD therapy is the delivery of inappropriate shocks, namely in response to supraventricular tachycardia and atrial fibrillation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the summary estimate of clinical data and outcome is based on 16 studies. 4,7,9,[12][13][14]16,[18][19][20][24][25][26][27][28]30 Thirteen (81%) studies reported on a population of patients with HCM with an ICD for primary or secondary prevention of SCD, 1 (8%) study focused on patients with HCM with an ICD for primary prevention of SCD, and 2 (13%) studies reported on patients with hypertrophic obstructive cardiomyopathy who underwent alcohol septal ablation and had received an ICD.…”
Section: Search Resultsmentioning
confidence: 99%
“…The central role of ventricular arrhythmias in the pathogenesis of SCD in HCM is supported by the observation that HCM patients treated with ICD receive appropriate therapies. [10][11][12][13][14][15][16][17][18] Systematic analysis of stored electrograms shows that the majority of ventricular arrhythmias occur while in normal sinus rhythm and are precipitated by premature ventricular complexes. 19 In addition, data from chance electrocardiographic recordings have shown that ventricular fibrillation can be precipitated by runs of ventricular tachycardia, rapid atrial fibrillation (AF), or accelerated atrioventricular conduction.…”
Section: Sudden Cardiac Death and Underlying Mechanismsmentioning
confidence: 99%